Determinación de la eficiencia agronómica del cultivo de cacao ccn-51 (Theobroma cacao) utilizando cuatro fertilizantes foliares en el cantón Caluma - Erazo Zumba, Fernando Gastón (2025)
The study focused on evaluating the agronomic efficiency of the CCN-51 cocoa crop through the application of different foliar fertilizers. The objectives were: i) To establish which of the treatments used presented the best agronomic characteristics in the crop. ii) To identify the effects of foliar fertilization on flowering and fruit set. iii) To generate a database of agronomic traits, as a basis for continuity in future research. The study was developed over a period of four months and used descriptive and inferential statistical analysis that included Fisher tests with significance levels of 5% and 1%, as well as the Tukey test at 5% for multiple comparisons of means, considering maximum, minimum and general mean values. A controlled experiment was carried out with five different treatments: Evergreen, Fertiquel, Nektar, Florone and a control group without application of foliar fertilizer. Data were recorded before and four months after application. The variables evaluated were: number of flower buds per plant, number of open flowers per plant, number of semi-open flowers per plant, number of set flowers per plant, number of small ears per plant, number of medium ears per plant, number of large ears per plant, length of small ears per plant, length of medium ears per plant, length of large ears per plant, diameter of small ears per plant, diameter of medium ears per plant, diameter of large ears per plant, number of branches per plant, length of branches per plant, diameter of branches per plant, number of ears with monilla, number of black ears and number of fruits. The results indicated that foliar fertilizer application had a significant effect on fruit production of CCN-51 cacao. The Fertiquel treatment showed the highest values, which underscore the importance of carefully selecting the type of foliar fertilizer to optimize the yield and health of the CCN-51 cacao crop. It is recommended that additional studies be conducted in different geographical locations to adapt agronomic practices more efficiently.